2016
DOI: 10.5812/jjm.28923
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Aminoglycoside-Resistant Enterococcus faecalis Isolates Due to the aac(6’)-aph(2”) Gene: A Therapeutic Problem in Kermanshah, Iran

Abstract: Background:Enterococci are important pathogens in nosocomial infections. Various types of antibiotics, such as aminoglycosides, are used for treatment of these infections. Enterococci can acquire resistant traits, which can lead to therapeutic problems with aminoglycosides.Objectives:This study was designed to identify the prevalence of, and to compare, the aac(6’)-aph(2”) and aph(3)-IIIa genes and their antimicrobial resistance patterns among Enterococcus faecalis and E. faecium isolates from patients at Imam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
11
2
Order By: Relevance
“…In this study, the most prevalent aminoglycoside resistance gene among the HLGR isolates was aph(3′)-IIIa (92.6%), and the aac(6′)-Ie-aph(2′′)-Ia gene was found in 62.9% of them (Table II). It was contrary to previous studies that the aac (6′)-Ie-aph(2′′)-Ia gene has been characterized as the main aminoglycoside [30][31][32]. In a study conducted in Tehran, north of Iran, the aac(6′)-Ie-aph(2′′)-Ia and ant(4′)-Ia genes were detected in HLGR enterococci [30].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this study, the most prevalent aminoglycoside resistance gene among the HLGR isolates was aph(3′)-IIIa (92.6%), and the aac(6′)-Ie-aph(2′′)-Ia gene was found in 62.9% of them (Table II). It was contrary to previous studies that the aac (6′)-Ie-aph(2′′)-Ia gene has been characterized as the main aminoglycoside [30][31][32]. In a study conducted in Tehran, north of Iran, the aac(6′)-Ie-aph(2′′)-Ia and ant(4′)-Ia genes were detected in HLGR enterococci [30].…”
Section: Discussionmentioning
confidence: 80%
“…Our results indicated that 50.9% of isolates were HLGR (MIC ≥ 500 μg/ml). In the several studies, high-level gentamicin resistance among E. faecalis isolates was reported in 65%-96% of the strains [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes conferred resistance to β‐lactams ( pbp4 ), vancomycin ( vanB ), chloramphenicol ( cat ), macrolides ( ermB ), tetracycline ( tetM , tetL ), aminoglycosides ( acc6‐aph2 , aph(3)‐III , aant(4)Ia ) and ciprofloxacin ( gyrA , pyrC ) were characterized as described earlier (Araújo et al, ; Khani et al, ; Zahid, Bin‐Asif, Hasan, Rehman, & Ali, ). Primer sets, PBP4‐f 5′‐CCA‐CTT‐ATT‐CTT‐GGT‐GTT‐TCT‐G‐3′ and PBP4‐r 5′‐CTT‐TCA‐TTT‐CGC‐CTA‐AAG‐GAG‐TG‐3′ for the detection of penicillin binding protein ( pbp4 ) was design from reference sequence (GenBank: AJ290435.1).…”
Section: Methodsmentioning
confidence: 99%
“…Enterococcus faecalis is a commensal organism found in poultry and the human gastrointestinal tract. In recent years, E. faecalis has emerged as a major zoonotic and nosocomial pathogen (~70%–80% cases) which infects animals and humans alike (Khani, Fatollahzade, Pajavand, Bakhtiari, & Abiri, ; Semedo‐Lemsaddek, Tavares, São Braz, Tavares, & Oliveira, ). Indeed, the dual nature of Enterococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…PCR and MLST. PCR amplification of the 16S rRNA gene, MLST housekeeping genes, tetS, tetM, aph(3=)-IIIa, and aac(6=)-aph(2Љ) was performed using previously published primers and protocols (Table 7) (38)(39)(40)(41)(42). PCR primers for mutL and str were designed using the Primer-BLAST tool (https://www.ncbi .nlm.nih.gov/tools/primer-blast/).…”
Section: Methodsmentioning
confidence: 99%